Ground state in a half-doped manganite distinguished by neutron spectroscopy. - Johnstone, G; Perring, T; Sikora, O; Prabhakaran, D; Boothroyd, A (2012)
We have measured the spin-wave spectrum of the half-doped bilayer manganite Pr(Ca,Sr)(2)Mn(2)O(7) in its spin, charge, and orbital ordered phase. The measurements, which extend throughout the Brillouin zone and cover the entire one-magnon spectrum, are compared critically with spin-wave calculations for different models of the electronic ground state. The data are described very well by the Goodenough model, which has weakly interacting ferromagnetic zig-zag chains in the CE-type arrangement. A model that allows ferromagnetic dimers to form within the zigzags is inconsistent with the data. The analysis conclusively rules out the strongly bound dimer (Zener polaron) model.